Marine Mammal HiCUP: A High Current Underwater Platform for the Long-Term Monitoring of Fine-Scale Marine Mammal Behavior Around Tidal Turbines - Gillespie, Douglas; Oswald, Michael; Hastie, Gordon; Sparling, Carol (Frontiers in Marine Science, 2022)
Arrays of tidal turbines are being considered for tidally energetic coastal sites which can be important habitat for many species of marine mammal. Understanding risks to marine mammals from collisions with moving turbine blades must be overcome before regulators can issue licenses for many developments. To understand these risks, it is necessary to understand how animals move around operational turbines and to document the rate at which interactions occur. We report on the design, and performance, of a seabed mounted sensor platform for monitoring the fine scale movements of cetaceans and pinnipeds around operational tidal turbines. The system comprises two high-frequency multibeam active sonars, which can accurately track animals in the horizontal plane. By offsetting the vertical angle of the sonars, the relative intensity of targets on the two sonars can also be used to resolve a vertical component of the animal location. For regularly vocalizing species, i.e., small cetaceans, a tetrahedral array of high frequency hydrophones mounted close to the sonars is used to measure both horizontal and vertical angles to cetacean echolocation clicks. This provides additional localization and tracking information for cetaceans and can also be used to distinguish between pinnipeds and cetaceans detected in the sonar data, based on the presence or absence of echolocation clicks. The system is cabled to shore for power, data transfer, and communications using turbine infrastructure. This allows for continuous operation over many months or years, which will be required to capture what may be rare interactions. The system was tested during a series of multi-week field tests, designed to test system integrity, carry out system calibrations, and test the efficiency of data collection, analyses, and archiving procedures. Overall, the system proved highly reliable, with the PAM system providing bearing accuracies to synthetic sounds of around 4.2 degrees for echolocation clicks with a signal to noise ratio above 15 dB. The system will be deployed close to an operational turbine in early 2022.